Biotransformation of beta blocker PhAC by nitrifying and denitrifying communities: Experimental and modeling investigation of cometabolism and metabolism - Hunter, Amy. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Civil Engineering.; Advisor: Andrew Ramsburg.; Committee: Laurie Baise, Amy Pickering, and Wayne Chudyk.; Keyword: Environmental engineering.